ANALISIS PELAKSANAAN STRATEGI PEMBELAJARAN INKUIRI OLEH GURU PENDIDIKAN AGAMA KRISTEN DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS XI SMK NEGERI 1 LAGUBOTI KABUPATEN TOBA SAMOSIR TAHUN PEMBELAJARAN 2019/2020 - Desta Hutabarat (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The research aims is to know the level of propensity for the implementation of inquiry learning strategies by PAK teachers in improving on student learning activeness in grade XI SMK Negeri 1 Laguboti Toba Samosir in 2019/2020.                 The population is all students of class XI SMK Negeri 1 Laguboti Toba Samosir in 2019/2020 amounted to 233 people and sample in this study 30% of the population were 70 people. The sampling technique uses a random sampling technique. The instrument used in this study was a closed questionnaire that was tested on 30 students outside the study sample of 38 items. From the results of the instrument validity test as many as 35 items are valid and 3 items are invalid, thus as many as 35 items are used as research instruments.               Then the tendency level of the implementation of inquiry learning strategies by PAK teachers in improving on student learning activeness in grade XI SMK Negeri 1 Laguboti Toba Samosir in 2019/2020 is in a fairly good category of 38.57% and 61.43% again obtained from other inherent factors that is not examined in this study.  Keywords : Analysis of Implementation of Inquiry Learning Strategies by PAK Teachers in Improving Learning Activeness